In the Search of Radical Czech Democracy. Karel Kosík and the Philosophy of (Czech) History - Andělová, Kristina; Mareš, Jan (Dějiny – teorie – kritika, 2014)
This paper investigates the conceptualization of the philosophy of (Czech) history in the early work of Czech philosopher Karel Kosík. Although Kosík’s historical narrative has later been interpreted predominantly as forming the very opposite of Zdeněk Nejedlý’s notions, authors show that Kosík’s texts from the 1950s were strongly infl uenced by Nejedlý’s interpretation of Czech progressive traditions and in a dialogical way represented a serious attempt to rethink Nejedlý’s views. Indeed, Kosík’s main historical synthesis Czech Radical Democracy (1958) was the result of such an endeavour and to certain extent anticipated his revisionist period which was soon to come. In this book, Kosík revised his Marxist methodology towards a consistent application of a historical materialism and abandoned the effort to present a coherent philosophy of Czech history as Nejedlý did. Secondly, the authors explain why Kosík’s interest in revolutionary democrats may have been perceived by his contemporaries as innovative. The origins of the notion ‘radical democracy’ or ‘radical democrats’ can be traced all the way back to the revolutionary events of 1848. Second part of the text describes how the notion of radical democracy gradually established itself in the Czech historical discourse and how it became the subject of various controversies. Kosík is thus presented here not as a creator or pioneer of this concept but rather as someone whose work refl ected many previous interpretations, especially those produced during interwar period. What is new in Kosík’s attitude is his attempt to present Czech radical democracy as a coherent political stream with its own historical logic.